Chlamydia, Gonorrhea, and Incident HIV Infection During Pregnancy Predict Preterm Birth Despite Treatment. (23rd May 2021) - Ravindran, Jayalakshmi; Richardson, Barbra A; Kinuthia, John; Unger, Jennifer A; Drake, Alison L; Osborn, Lusi; Matemo, Daniel; Patterson, Janna; McClelland, R Scott; John-Stewart, Grace
Abstract: Background: Identifying predictors of preterm birth (PTB) in high-burden regions is important as PTB is the leading cause of global child mortality. Methods: This analysis was nested in a longitudinal study of human immunodeficiency virus (HIV) incidence in Kenya. HIV-seronegative women enrolled in pregnancy had nucleic acid amplification tests (chlamydia and gonorrhea), rapid plasma reagin (syphilis), wet mount microscopy (Trichomonas and yeast), and Gram stain (bacterial vaginosis); sexually transmitted infection (STI) treatment was provided. PTB predictors were determined using log-binomial regression. Results: Among 1244 mothers of liveborn infants, median gestational age at enrollment was 26 weeks (IQR, 22–31), and at delivery was 39.1 weeks (IQR, 37.1–40.9). PTB occurred in 302 women (24.3%). Chlamydia was associated with a 1.59-fold (P = .006), gonorrhea a 1.62-fold (P = .04), and incident HIV a 2.08-fold (P = .02) increased PTB prevalence. Vaginal discharge and cervical inflammation were associated with PTB, as were age ≤21 (prevalence ratio [PR] = 1.39, P = .001) and any STI (PR = 1.47, P = .001). Associations with chlamydia and incident HIV remained in multivariable models. Conclusions: STIs and incident HIV in pregnancy predicted PTB despite treatment, suggesting the need for earlier treatment and interventions to decrease genital inflammation. Abstract : Pregnant women with chlamydia, gonorrhea, and incident HIV infection had increased risk of preterm birth. Delays in diagnosis and treatment likely attenuated treatment benefit. Point-of-care testing for sexually transmitted infections with same-day treatment may be useful to prevent preterm birth.